2016
DOI: 10.1096/fj.201600296rrr
|View full text |Cite
|
Sign up to set email alerts
|

A reverse genetics cell‐based evaluation of genes linked to healthy human tissue age

Abstract: We recently developed a binary (i.e., young vs. old) classifier using human muscle RNA profiles that accurately distinguished the age of multiple tissue types. Pathway analysis did not reveal regulators of these 150 genes, so we used reverse genetics and pharmacologic methods to explore regulation of gene expression. Using small interfering RNA, well-studied age-related factors (i.e., rapamycin, resveratrol, TNF-α, and staurosporine), quantitative real-time PCR and clustering analysis, we studied gene–gene int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…The expression of LAMTOR5 was not regulated by exercise, yet Figure 6 reveals parts of the LAMTOR 5 “interactome” relate to muscle activity (e.g., PRDX1 interacts with TXNL1 , and MTRF1 interacts with LAMTOR5 ). These interactions can be explored further using reverse genetic strategies and pharmacological tools in human primary cells ( Crossland et al., 2017a ).
Figure 5 Genes Regulated by Potentially Related Physiological Conditions Show Substantial Pathway Overlap (A and B) Circos plots showing the overlap in gene expression (A) and Gene Ontology (B) between the HypAt model and additional biological signatures of potentially related physiological conditions (e.g., insulin sensitivity; RT [resistance training]; age; ET [endurance training]).
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of LAMTOR5 was not regulated by exercise, yet Figure 6 reveals parts of the LAMTOR 5 “interactome” relate to muscle activity (e.g., PRDX1 interacts with TXNL1 , and MTRF1 interacts with LAMTOR5 ). These interactions can be explored further using reverse genetic strategies and pharmacological tools in human primary cells ( Crossland et al., 2017a ).
Figure 5 Genes Regulated by Potentially Related Physiological Conditions Show Substantial Pathway Overlap (A and B) Circos plots showing the overlap in gene expression (A) and Gene Ontology (B) between the HypAt model and additional biological signatures of potentially related physiological conditions (e.g., insulin sensitivity; RT [resistance training]; age; ET [endurance training]).
…”
Section: Discussionmentioning
confidence: 99%
“…Human primary skeletal muscle cells were isolated from muscle biopsies from healthy young adults and cultured as previously described ( Crossland et al., 2017a , 2017b ). Myogenic cell enrichment was carried out using magnetic-activated cell sorting (MACS), using anti-CD56 microbeads and myoblasts were used for experimentation at passage 5-6.…”
Section: Methodsmentioning
confidence: 99%
“… Fang et al (2017) predicted possible other targets of interest for the anti-cancer effects of resveratrol based on statistical analysis of publicly available databases of deposited bioactivity (such as ChEMBL, Binding DB, and TCGA) combined with by machine learning. Crossland et al (2017) observed that while resveratrol did reverse transcription of genes that are the most perturbed due to aging in patient derived muscle cells and tissue, it did not reverse the disease (aging) gene signature when they observed the effect at a systems level. Interestingly, the authors state that based on their findings, SIRT1 and AMPK may not be a regulator of healthy aging, further explaining the lack of translational activity for resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LAMTOR5 was not regulated by exercise, yet Figure 6 reveals parts of the LAMTOR5 ''interactome'' relate to muscle activity (e.g., PRDX1 interacts with TXNL1, and MTRF1 interacts with LAMTOR5). These interactions can be explored further using reverse genetic strategies and pharmacological tools in human primary cells (Crossland et al, 2017a).…”
Section: Leveraging Transcriptional Network To Investigate Chronic Disease and Identify Potential Therapiesmentioning
confidence: 99%
“…Human primary skeletal muscle cells were isolated from muscle biopsies from healthy young adults and cultured as previously described (Crossland et al, 2017a(Crossland et al, , 2017b. Myogenic cell enrichment was carried out using magnetic-activated cell sorting (MACS), using anti-CD56 microbeads and myoblasts were used for experimentation at passage 5-6.…”
Section: Human Primary Muscle Cell Culturementioning
confidence: 99%